Investigation of Inertial Cavitation of Sonosensitive and Biocompatible Nanoparticles in Flow - Through Tissue- Mimicking Phantoms Employing Focused Ultrasound - George, Benedikt; Savsek, Ula; Fischer, Dagmar; Ermert, Helmut; Rupitsch, Stefan J. (Current Directions in Biomedical Engineering, 2021)
A promising approach to drug delivery applications for chemotherapeutics is the use of drug carriers to reduce the total amount of cytostatics, minimizing side effects. In addition, the carriers, loaded with the drug, can be guided to the tumorous tissue via the vascular system, which enables a local drug release (LDR). In our case, LDR is activated due to the sonosensitive behavior of the nanocapsules by inertial cavitation (IC) caused by focused ultrasound (FUS). Thereby, IC is excited by employing sound pressures within the recommended limit allowed for diagnostic ultrasound. In order to verify this drug delivery approach for its clinical suitability, a tissue-mimicking flow -through phantom, containing a small vessel, is used. Investigations have shown that the drug releasing cavitation effect associated with the sonosensitive and biocompatible nanocapsules also occurs in fine vessel structures, even in the case of moving particles and vessel diameters dc smaller than the wavelength λ.
CRIS-Team Scopus Importer:2024-12-16
Keywords: flow - through.; Inertial cavitation; nanoparticles; tissue - mimicking phantom